Maternal and neonatal risk factors of asthma in children: Nationwide population based study - Chuang-Ming Wang; Shun-Ting Yang; Cheng-Chia Yang; Hsiao-Yu Chiu; Hsiang-Yu Lin; Ming-Luen Tsai; Hung-Chih Lin; Yu-Chia Chang (Journal of Microbiology, Immunology and Infection, 2023)
Background: Small population group-based cohorts have found that perinatal factors may contribute to the development of asthma in children. We aimed to investigate maternal and neonatal risk factors for the asthma phenotypes using two databases from the Taiwan's Maternal and Child Health Database (TMCHD) and the National Health Insurance Research Database (NHIRD). Methods: Perinatal data was obtained from 2004 to 2008 in the TMCHD and linked the NHIRD to obtain relevant medical information regarding maternal and neonatal risk factors of three asthma phenotypes which were identified as transient early asthma, persistent asthma, and late-onset asthma. A multivariate logistic regression analysis was conducted to adjust for covariates. Results: The percentage of non-asthmatic patients was 77.02% and asthmatic (transient early asthma, late onset asthma, and persistent asthma) patients were 8.96%, 11.64%, and 2.42%, respectively. Maternal risk factors—including Cesarean section, maternal asthma, maternal allergic rhinitis (AR), and premature rupture of membranes—and neonatal risk factors, such as male gender, gestational age 29–37 weeks, ventilator use, antibiotics use, AR, and atopic dermatitis, were associated with the development of these three asthma phenotypes. Twins and a gestational age of 28 weeks or less premature were associated with the development of transient early asthma and persistent asthma, but not late onset asthma. Triplets and above were associated with the development of transient early asthma, but not late onset or persistent asthma. Conclusion: Various asthma phenotypes have different risk factors; therefore, their distinct risk factors should be identified in order to early diagnosis and treatment.